Microminerais orgânicos, cálcio quelatado ou de alga sobre o desempenho, qualidade de ovo, incubação e qualidade espermática em reprodutores avícolas - Londero, Angélica (2019)
The objective of this study was evaluate the effect of the effects of the supplementation of organic micro minerals (OMM) added to inorganic minerals and calcium amino acid chelated or marine calcium calcium (Lithothamnium calcareum) on the performance, egg quality, incubation and sperm quality of poultry breeding. Two studies were performed, described in Chapters II and III. In both experiments, females were artificially inseminated once a week with semen from males submitted to the same diet and the data were submitted to ANOVA and Tukey’s test. In chapter II: SUPPLEMENTATION OF ORGANIC MINERALS AND INORGANIC ON THE PERFORMANCE, EGG AND SPERM QUALITY AND, HATCHING CHARACTERISTICS OF LAYING BREEDER HENS, there were used 144 White Plymouth Rock females and 36 Red Rhodes Island males at 36 to 55 weeks of age in the experimental design completely randomized, with 8 replicates with 6 hens and 12 replicates with 1 male each. The treatments evaluated were: DB - basal diet containing only inorganic mineral (10mg Cu, 60mg Fe, 70mg Mn, 75mg Zn and 0,3mg Se per kg of diet), BD + 500gOMM - basal diet plus 500g of organic mineral by ton of diet (2.5mg Cu, 17.5mg Fe, 20mg Mn, 27.5mg Zn and 0.08mg Se by kg of diet) and BD + 800gOMM - basal diet plus 800g of organic mineral per ton of diet (4mg Cu, 28mg Fe, 32mg Mn, 44mg Zn and 0.128mg Se per kg of diet). In the weeks 43, 44, 45 and 49 the eggs production was higher in treatment BD+800gOMM than BD. The yolk index was better in eggs from hens fed with treatment BD than BD+800gOMM. The sperm vigor in the males fed with treatment BD+800gOMM was higher than BD. The fertility was higher in eggs from hens fed with treatment BD+500gOMM than BD. In chapter III: SUPPLEMENTATION OF ORGANIC MICRO MINERALS AND CALCIUM OF AMINO ACID CHELATED OR MARINE CALCIUM (Lithothamnium calcareum) ON THE PRODUCTIVE AND REPRODUCTIVE CHARACTERISTICS OF LAYING BREEDER HENS, there were used 192 Plymouth Rock White females and 48 Rhodes Island Red males at 36 to 55 weeks of age in the randomly distributed in a factorial arrangement (2 × 2) totaling 8 replicates with 6 hens and 12 replicates with 1 male each. From a basal diet containing inorganic minerals were made 4 diets of 2 levels of organic trace minerals: 500OMM - 500g of the organic minerals by ton of diet (2.5 mg Cu, 17.5mg Fe, 20mg Mn, 27.5mg Zn and 0.08mg Se per kg of diet) and 800OMM - 800g of the organic minerals by ton of diet (4mg Cu, 28mg Fe, 32mg Mn, 44mg Zn and 0.128mg Se per kg of diet) and 2 types of calcium: calcium amino acid chelated (CaCh) – 0.155g/kg and calcium from Lithothamnium calcareum (LCa) algae – 1.6g/kg of diet. An increase in the yolk, eggshell, specific gravity and shell thickness were observed in eggs from hens fed with Cah. An increase in the albumen was observed in eggs from hens fed LCa. Sperm volume was higher in males fed with 500OMM. Motility and sperm vigor were improved in males fed with CaCh on diets. Incubation parameters were not affected by treatments. In conclusion, the addition of organic minerals in the diet brought positive effects with increased egg production, fertility and vigor of sperm from males. The calcium amino acid chelated has positive effects on quality of egg, motility and sperm vigor.